Effects of Quinine, Quinidine and Chloroquine on Human Muscle Nicotinic Acetylcholine Receptors - Gisselmann, Günter; Alisch, Desiree; Welbers-Joop, Brigitte; Hatt, Hanns (Frontiers in Pharmacology, 2018)
The genus Cinchona is known for a range of alkaloids, such as quinine, quinidine, cinchonine, and cinchonidine. Cinchona bark has been used as an antimalarial agent for more than 400 years. Quinine was first isolated in 1820 and is still acknowledged in the therapy of chloroquine-resistant falciparum malaria; in lower dosage quinine has been used as treatment for leg cramps since the 1940s. Here we report the effects of the quinoline derivatives quinine, quinidine, and chloroquine on human adult and fetal muscle nicotinic acetylcholine receptors (nAChRs). It could be demonstrated that the compounds blocked acetylcholine (ACh)-evoked responses in Xenopus laevis oocytes expressing the adult nAChR composed of alpha beta epsilon delta subunits in a concentration-dependent manner, with a ranked potency of quinine (IC50 = 1.70 µM), chloroquine (IC50 = 2.22 µM) and quinidine (IC50 = 3.96 µM). At the fetal nAChR composed of alpha beta gamma delta subunits, the IC50 for quinine was found to be 2.30 µM. The efficacy of the block by quinine was independent of the ACh concentration. Therefore, quinine is proposed to inhibit ACh-evoked currents in a non-competitive manner. The present results add to the pharmacological characterization of muscle nicotinic acetylcholine receptors and indicate that quinine is effective at the muscular nAChRs close to therapeutic blood concentrations required for the therapy and prophylaxis of nocturnal leg cramps, suggesting that the clinically proven efficacy of quinine could be based on targeting nAChRs.